Human Rights: Methods and Models of Education and Teaching - Ali Mohammed , Dr. Abbas (Basra studies journal, 2024)
One of the most important means and tools used in spreading the culture and principles of human rights is through education and teaching. This is because such a method or tool deals with and interacts with a wide range of young people, who are the most dynamic and influential segment of society. They will be the actual leading segment of the future. Therefore, the attention to this process is one of the most important tools for disseminating the culture of human rights and transforming it from principles and methodologies into daily behaviour within the reality of life. This will increase the chances of success in reducing the occurrence of violations, as well as the possibility of promoting a spirit of peaceful coexistence, acceptance of others, rejection of violence, and ensuring the requirements of the right to life for all without discrimination.